2017
DOI: 10.1001/jamasurg.2016.3642
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Optimal Time Interval to Re-resection for Incidental Gallbladder Cancer With Overall Survival

Abstract: IMPORTANCE The current recommendation is to perform re-resection for select patients with incidentally discovered gallbladder cancer. The optimal time interval for re-resection for both patient selection and long-term survival is not known. OBJECTIVE To assess the association of time interval from the initial cholecystectomy to reoperation with overall survival. DESIGN, SETTING, AND PARTICIPANTS This cohort study was conducted from January 1, 2000, to December 31, 2014 at 10 US academic institutions. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Most GBC patients are at an advanced stage once confirmed and lose the opportunity for surgical treatment [3]. Fortunately, with the development of laparoscopy, an increasing number of GBCs may be confirmed at the early stage through laparoscopic cholecystectomy (LC) so that early R0 resection may be performed; thus, progression of the disease may be avoided, and the overall survival rate may be improved [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most GBC patients are at an advanced stage once confirmed and lose the opportunity for surgical treatment [3]. Fortunately, with the development of laparoscopy, an increasing number of GBCs may be confirmed at the early stage through laparoscopic cholecystectomy (LC) so that early R0 resection may be performed; thus, progression of the disease may be avoided, and the overall survival rate may be improved [4,5].…”
mentioning
confidence: 99%
“…More than 50% of GBCs are diagnosed by intraoperative or postoperative pathological examination after LC [4] and are considered incidental gallbladder cancer (IGBC), in which stage T1/2 GBCs are the most common [6]. IGBC often requires radical re-resection [5].…”
mentioning
confidence: 99%
“…As such, the data were likely a good representation of the current state of treatment of extrahepatic biliary cancers, with a higher level of detail than can be achieved using national databases. [11, 2429] Finally, data on the degree/severity of the SSI was not available and therefore a “dose effect” of SSI on RFS could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no prospective, large-sample randomized controlled trials indicating an acceptable interval between primary surgery and secondary radical surgery. In a large-sample retrospective study in 2017, Ethun et al (30) suggested that secondary radical surgery for incidental T1b and T2 GBC should be performed within 4-8 weeks after primary surgery to improve prognosis. Prior to 4 weeks, inflammation, edema, and adhesions caused by the primary surgery will affect radical surgery, while the rate of an R1 or R2 resection increases significantly (p = 0.05 and < 0.001).…”
Section: Secondary Cure: Indications and Timingmentioning
confidence: 99%